A Novel Complex: A Quantum Dot Conjugated to an Active T7 RNA Polymerase. (19th May 2013) - Eriksen, Mette; Horvath, Peter; Sørensen, Michael A.; Semsey, Szabolcs; Oddershede, Lene B.; Jauffred, Liselotte
Abstract : To perform single-molecule studies of the T 7 RNA polymerase, it is crucial to visualize an individual T 7 RNA polymerase, for example, through a fluorescent signal. We present a novel complex combining two different molecular functions, an active T 7 RNA polymerase and a highly luminescent nanoparticle, a quantum dot. The complex has the advantage of both constituents: the complex can traffic along DNA and simultaneously be visualized, both at the ensemble and at the single-molecule level. The labeling was mediated through an in vivo biotinylation of a His-tagged T 7 RNA polymerase and subsequent binding of a streptavidin-coated quantum dot. Our technique allows for easy purification of the quantum dot labeled T 7 RNA polymerases from the reactants. Also, the conjugation does not alter the functionality of the polymerase; it retains the ability to bind and transcribe.